2019
DOI: 10.1152/physrev.00061.2017
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia: Aging-Related Loss of Muscle Mass and Function

Abstract: Sarcopenia is a loss of muscle mass and function in the elderly that reduces mobility, diminishes quality of life, and can lead to fall-related injuries, which require costly hospitalization and extended rehabilitation. This review focuses on the aging-related structural changes and mechanisms at cellular and subcellular levels underlying changes in the individual motor unit: specifically, the perikaryon of the α-motoneuron, its neuromuscular junction(s), and the muscle fibers that it innervates. Loss of muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
828
1
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 959 publications
(873 citation statements)
references
References 961 publications
25
828
1
19
Order By: Relevance
“…Indeed, it is well documented that the deterioration of gait speed related to sarcopenia during aging is due to quantitative and qualitative changes in muscle structure and function. 1 We also found that the lower the gait speed, the greater dependency, which is in accord with the literature on this topic, 6,33 in which a lower gait speed is related to more problems in ADL. Accordingly, physical activity focused on counteracting the decline in gait speed could prevent functional dependency.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, it is well documented that the deterioration of gait speed related to sarcopenia during aging is due to quantitative and qualitative changes in muscle structure and function. 1 We also found that the lower the gait speed, the greater dependency, which is in accord with the literature on this topic, 6,33 in which a lower gait speed is related to more problems in ADL. Accordingly, physical activity focused on counteracting the decline in gait speed could prevent functional dependency.…”
Section: Discussionsupporting
confidence: 90%
“…Sarcopenia is an age‐related loss of muscle mass and function in older adults and may favour the appearance of cardiovascular complications or neurodegenerative disorders. While its prevalence is variable depending on its localization and the method of evaluation, it is estimated that 29% of older persons in community‐dwelling populations and 14–33% in long‐term care populations are affected by sarcopenia .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle atrophy is a well-known consequence of the ageing process and is the result of both a reduction in muscle fibre number and selective atrophy of the remaining muscle fibres (Larsson et al 2019). It is often noted that different muscle fibre types are affected by the atrophy process to different degrees, with many studies concluding that type II fibres atrophy more than do type I fibres with ageing (Lexell et al 1988;Nilwik et al 2013;St-Jean-Pelletier et al 2017).…”
Section: Changes In Muscle Fibre Size and Proportion With Advanced Agementioning
confidence: 99%
“…
Skeletal muscle mass and function decline progressively during ageing. Since this is associated with susceptibility to chronic diseases, metabolic dysfunction, physical frailty and an overall reduction in quality of life, age-related loss of muscle function negatively affects the daily life of millions of people (Larsson et al 2019). To battle age-related loss of muscle function, improving our understanding of the underlying cellular mechanisms is crucial.Altered mitochondrial protein homeostasis during ageing has been proposed to mediate the age-related loss of muscle function.
…”
mentioning
confidence: 99%